Circular flow: universal and local in the Imperium Galliarum - Christensen, Kristian Kanstrup (Classica et Mediaevalia, 2025)
This article investigates the cultural tendencies of the Gallic Empire (c. AD 260-274). The persistence of imperial institutions shows the Gallic emperors intended to convey an impression of continuity. Yet the numismatic record also shows the influence of a distinct cultural environment associated with the Batavian community and the Rhine army. Batavian forms of Hercules, originally developed through the transformation of the Roman Hercules to suit a local context, were elevated into Postumus’ (r. c. AD 260 to 269) imperial propaganda, confirming a long-held hypothesis in anthropology postulating a circular flow of cultural borrowing in agrarian societies between local and elite traditions.